The Role of Ginsenosides in Myocardial Ischemic Injury-A Systematic Review - Wenhao, Song; Quanwei, Wang; Wenwen, Fu; Ce, Zhang; Tian, Wang (Asian Journal of Pharmaceutical Research and Development, 2022)
Topical herbal formulations are gaining more attention in wound healing due to their safety and efficacy. This is a systematic review of the effects of Curcuma longatopical formulations on wound healing. C. longa is a traditional medicinal plant used due to its antimicrobial, antioxidant, anti-inflammatory, and wound healing properties. Studies carried outas randomized control trials and clinical trials were included for the analysis of this review. Searches were conducted in PubMed, Scopus, Cochrane Central Register of Controlled Trials, and Google scholar (up to March 2022) with 04 studies meeting the inclusion criteria. All randomized control trials and clinical trials have shown a significant improvement in wound healing. The topical formulations containing C. longa as an ingredient have reportedly improved wound healing in cases of eczema, radiodermatitis, acne vulgaris, atopic dermatitis, ichthyosis vulgaris, senile pruritis, and xerotic skin conditions, according to the studies covered in this review.This review identified some evidence that C. longa extract has good effects for wound healing, in accordance with its use in traditional medicine. To evaluate the impact of C. longa on wound healing, including complications, larger, well-designed randomized control trials are required.